Structure amid the Chaos: The Quadruple Structure in Guillaume Postel's Thought - Weiss, Judith (The journal of religion, 2019)
The article discusses the relation of Kabbalistic thought to the works of writer Guillaume Postel. Topics include the notion of quadrulple structures in Postel's writing, Postel's thought on male and female aspects of the Godhead, and the coherence of Postel's thought in relation to his commentary on the works of the Jewish author Zohar.